2020
DOI: 10.3390/ijerph17041341
|View full text |Cite
|
Sign up to set email alerts
|

Making Health Services Adolescent-Friendly in Northeastern Peninsular Malaysia: A Mixed-Methods Study

Abstract: A mixed-methods study was conducted in a Malaysian state beginning with a cross-sectional quantitative study to determine the relationship between clinic characteristics and clinic score of adolescent-friendliness. Subsequently, perceptions of healthcare providers on the facilitating factors for the provision of adolescent-friendly health services were explored qualitatively to support the quantitative findings. Availability of trained healthcare providers, adequate privacy, dedicated adolescent health service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
(36 reference statements)
2
7
0
2
Order By: Relevance
“…Another point highlighted was related to the adolescents seeking privacy in health appointments and confidentiality of the information provided there, elements reiterated in the literature, added to the relevance of listening and establishment of a reference professional (43) .…”
Section: Discussionmentioning
confidence: 99%
“…Another point highlighted was related to the adolescents seeking privacy in health appointments and confidentiality of the information provided there, elements reiterated in the literature, added to the relevance of listening and establishment of a reference professional (43) .…”
Section: Discussionmentioning
confidence: 99%
“…When coupled with the lack of knowledge and awareness of health problems related to menstruation among these girls, they experience further reduction in the utilisation of health care services [ 40 , 46 ]. Finally, the Ministry of Health, Malaysia has reported that current adolescent health services in Malaysia are not adolescent-friendly [ 47 ] and are therefore underutilized [ 40 , 47 ]. Negative attitudes of healthcare providers and lack of privacy [ 41 ] were identified as some of the major barriers to the utilisation of adolescent health services.…”
Section: Discussionmentioning
confidence: 99%
“…When dealing with adolescents, highly trained, knowledgeable, and competent professionals are significantly better at relating to adolescents. Engaging with adolescents in managing their health problems requires training of various levels of healthcare personnel [ 47 ]. Unfortunately, only 4.62% of the Ministry of Health’s budget was dedicated to healthcare personnel training programs in adolescent health [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outro ponto destacado foi relativo aos adolescentes almejarem privacidade nas consultas de saúde e sigilo das informações ali confidenciadas, elementos reiterados na literatura, somado à relevância da escuta e estabelecimento de profissional de referência (43) .…”
Section: Discussionunclassified